AWAL MASUKNYA ISLAM DI SUMATRA (Perkembangan Pendidikan Islam masa awal di Sumatera Barat, lembaga & tokohnya) - Zulqarnain Tajuddin; Bahaking Rama; Abdul Kadir (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2023)
Islam entered Minangkabau between the 12th and 13th centuries AD, by two routes namely; route from Aceh and route from Malacca. Islam was introduced by preachers and Arab merchants who settled in eastern Minangkabau, especially in the watershed that disgorged into the center of the Minangkabau kingdom in the interior. The expansion of the Samudra Pasai kingdom into eastern Minangkabau was very influential for the intensive spread of Islam in this region and other Minangkabau regions. The process of Islamization took place peacefully, because it was introduced through local wisdom approaches of the community in the local cultural environment. Surau (as the oldest educational institution) for the Minangkabau people has a multidimensional function, not only functioning as a place for gathering, meetings and sleeping places but also functioning as an Islamic educational institution, Minangkabau society is an open society, meaning people who do not close themselves off to accept change. The movement for reforming Islamic education in Minangkabau, which was initially initiated by three Minangkabau clerics who had studied in Mecca, where they received wide acceptance among the Minangkabau community, including from among Islamic figures who manage educational institutions (Surau-Surau, etc.) ). These three figures brought renewal ideas that were obtained in Mecca, one of the understandings they received was the ideology of "Wahabiyah" which aims to cleanse Islam of all traditions/customs that conflict with the purity of Islamic teachings, but their movement did not run smoothly because they received challenges from indigenous defenders. As a result, the two groups were involved in a conflict which later became known as the Padri War (1803-1837). Despite the challenges, their movement continued to run according to the ideals of their struggle, so that from this renewal movement, they gave birth to famous great scholars, where they established or changed the "Surau (halaqah)" education system to the "Classical" system and became the center Islamic education throughout the Minangkabau region and its surroundings.